Koppen-Geiger and Thornthwaite climatic classification for the metropolitan region of the Cariri, Ceará - Vieira, Mirelle Tainá; Meireles, Ana C. M.; Oliveira, Carlos W. de; Nascimento, Maria T. B. do (Revista Geama, 2017)
The aim of the present work was to compare the Koppen-Geiger and Thornthwaite methods for Climatic Classification of the Metropolitan Region of Cariri, state of Ceará, Brazil. The study area comprises the nine municipalities in the metropolitan region of the Cariri, being Juazeiro de Norte, Crato, Barbalha, Caririaçu, Farias Brito, Missão Velha, Nova Olinda, Jardim and Santana do Cariri. The temperature and rainfall data for the metropolitan region of the Cariri were submitted to Koppen-Geiger and Thornthwait classification, in order to compare the results. All weather data on precipitation and monthly temperature comes from the Data-Climate website, which provides world-class weather data for cities. There is a paucity of information about the climatic temperature and humidity normal in all cities, since not all have rain stations and data published by official institutions. This makes it difficult for public planning for the application of resources, the need for technical assistance and the implementation of technologies for water abstraction, as well as for research. The Köppen-Geiser climate classification is simpler to employ, however, the Thornthwaite classification has a more detailed result on the site. According to the Koppen-Geiser classification, the nine municipalities present in the metropolitan region of the Cariri are classified as Aw savanna climate. For Thornthwait, they can be classified generally as B1, B3 and C2, around humid to moist subhumid.